Living on the edge : essays on the Chittagong Hill Tracts - Bhaumik, Subir; Guhaṭhākuratā, Meghanā; Basu Ray Chaudhury, Sabyasachi; South Asia Forum for Human Rights; Calcutta Research Group (Kathmandu : South Asia Forum for Human Rights ; [Calcutta] : Calcutta Research Group, 1997)
Contributed essays.
Includes bibliographical references (pages [279]-281) and index.
The university press
Keywords: Chittagong Hill Tracts (Bangladesh : Region).